Efficacy and safety of LAS41008 (dimethyl fumarate) in adults with moderate‐to‐severe chronic plaque psoriasis: a randomized, double‐blind, Fumaderm®‐ and placebo‐controlled trial (BRIDGE). (1st March 2017) - Mrowietz, U.; Szepietowski, J.C.; Loewe, R.; van de Kerkhof, P.; Lamarca, R.; Ocker, W.G.; Tebbs, V.M.; Pau‐Charles, I.
Summary: Background: Fumaric acid esters (FAEs) are recommended in international guidelines for induction and long‐term treatment of adults with moderate‐to‐severe chronic plaque psoriasis. The fixed combination Fumaderm ® is approved in Germany, with dimethyl fumarate (DMF) being the main active ingredient. Objectives: To assess the efficacy and safety of a new formulation of DMF (LAS41008), compared with placebo and Fumaderm ®, in adults with moderate‐to‐severe chronic plaque psoriasis. Methods: In this phase III, double‐blind, placebo‐controlled, noninferiority trial (BRIDGE, NCT01726933, EudraCT 2012‐000055‐13), patients were randomized to receive LAS41008, Fumaderm ® or placebo (2 : 2 : 1) for 16 weeks, uptitrating to a maximum daily DMF dose of 720 mg, depending upon individual response. The coprimary end points were the percentage of patients achieving ≥ 75% improvement in Psoriasis Area and Severity Index (PASI 75) and the percentage achieving a score of 'clear' or 'almost clear' in the Physician's Global Assessment (PGA) at week 16. Results: In total, 671 patients were randomized and included in the full analysis set ( n = 267, LAS41008; n = 273, Fumaderm ® ; n = 131, placebo). At week 16, 37·5% of patients treated with LAS41008 achieved PASI 75, compared with 15·3% receiving placebo (superiority for LAS41008 vs. placebo: P < 0·001) and 40·3% receiving Fumaderm ® (noninferiority for LAS41008 vs. Fumaderm ® : P < 0·001). Overall, 33% of patients treated with LAS41008 were 'clear' or 'almost clear' in the PGA at week 16, compared with 13·0% receiving placebo ( P < 0·0001; LAS41008 superiority vs. placebo) and 37·4% receiving Fumaderm ® . Most treatment‐related adverse events were classed as 'mild' in severity. Conclusions: LAS41008 (DMF) is effective in the treatment of adults with moderate‐to‐severe chronic plaque psoriasis.